2001
DOI: 10.1603/0022-0493-94.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of Imidacloprid Seed Coating to <I>Bombus terrestris</I> (Hymenoptera: Apidae) When Applied to Sunflower

Abstract: Seed coating treatments of sunflower by the systemic insecticide imidacloprid was suspected of affecting honey bees and bumblebees. The hypothesis raised was whether imidacloprid could migrate into nectar and pollen, then modify flower attractiveness, homing behavior, and colony development. Our greenhouse and field experiments with Bombus terrestris L. were aimed at the following: the behavior of workers foraging on treated and control plants blooming in a greenhouse, the homing rate of colonies placed for 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 9 publications
2
43
0
Order By: Relevance
“…In particular, one group of persistent pesticides (the neonicotinoids) has been shown to be highly toxic to bees (EPA 1994;Marletto et al 2003) and has been implicated in bee declines in various regions in Europe (Tasei et al 2001). Its use in North America began in the early 1990s, before members of the subgenus Bombus were noted to be in decline, and thus this group of pesticides may be a substantial threat.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, one group of persistent pesticides (the neonicotinoids) has been shown to be highly toxic to bees (EPA 1994;Marletto et al 2003) and has been implicated in bee declines in various regions in Europe (Tasei et al 2001). Its use in North America began in the early 1990s, before members of the subgenus Bombus were noted to be in decline, and thus this group of pesticides may be a substantial threat.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although highly toxic by direct contact, the neonicotinoid insecticides are applied as seed treatments on canola, thus minimizing impact other than through possible minimal exposure to very low residues in nectar and pollen (Tasei et al 2001, Maus et al 2003, Cutler and Scott-Dupree 2007b. Conversely, although generally less toxic by contact, foliar applications of deltamethrin or spinosad could have immediate impact on foraging bees.…”
Section: Discussionmentioning
confidence: 99%
“…59 Observations on foraging activity of Bombus terrestris revealed no difference regarding the presence of workers on blooming heads and the duration of their visits between imidacloprid-treated and control sunflowers. 32 Another member of the chloronicotinyl family, clothianidin appeared harmless when colonies of B. impatiens were exposed to the highest residue levels in pollen, 60 or when hives of Apis mellifera were exposed to flowering canola grown from clothianidin-treated seeds. 61 Although these studies showed the absence of effect of neonicotinoids on foraging of treated plants, perturbations of the foraging behavior on artificial feeder were revealed in other experiments.…”
Section: Foraging and Feeding Behaviorsmentioning
confidence: 99%